2019
DOI: 10.1002/cncy.22114
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of nylon‐flocked swab and Dacron swab cytology for anal HSIL detection in transgender women and gay, bisexual, and other men who have sex with men

Abstract: Background An anal histological high‐grade squamous intraepithelial lesion (hHSIL) is an anal cancer precursor. Experts recommend Dacron swab anal cytology as a primary screen for anal hHSILs, especially among human immunodeficiency virus–infected and –uninfected men who have sex with men (MSM). Studies have shown that Dacron cytology inaccurately predicts anal hHSILs and results in unnecessary diagnostic procedures. Nylon‐flocked (NF) swabs have been shown to trap pathogens and cells well. Thus, this study co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
(97 reference statements)
0
3
0
1
Order By: Relevance
“…Briefly, 4717 articles were identified, after removal of duplicates (n = 863), 3748 were excluded based on title/abstract review. Of the remaining 106 articles, 39 were included after full‐text review (Table 1; Supplemental Material) 12‐50 . Most studies reported data for PLWH (n = 29), 12,13,15,16,18‐34,36‐39,41,43,47,50 a majority were among MSM LWH (n = 18) 12,13,15,16,21,25‐27,29,31‐34,36,38,39,47,50 .…”
Section: Resultsmentioning
confidence: 99%
“…Briefly, 4717 articles were identified, after removal of duplicates (n = 863), 3748 were excluded based on title/abstract review. Of the remaining 106 articles, 39 were included after full‐text review (Table 1; Supplemental Material) 12‐50 . Most studies reported data for PLWH (n = 29), 12,13,15,16,18‐34,36‐39,41,43,47,50 a majority were among MSM LWH (n = 18) 12,13,15,16,21,25‐27,29,31‐34,36,38,39,47,50 .…”
Section: Resultsmentioning
confidence: 99%
“…However, the study had a very small sample size and no correlation between cytology and histology was reported. A study by Wiley et al [26] (n = 58 MSM) suggested that flocked swabs were better able to predict histological anal HSIL; however, in a more recent study with a larger sample (326 subjects) [27], the sensitivity in predicting anal HSIL was similar between brushes. Thus far, studies have consistently failed to show that flocked nylon swabs are better than Dacron swabs.…”
Section: Type Of Brushmentioning
confidence: 92%
“…They are approved for use in the endocervical canal of women only [24] and can be uncomfortable in the anal canal. Several studies have compared Dacron swabs and flocked nylon swabs [25][26][27] in terms of the number of cells collected and the performance of anal cytology compared with histology.…”
Section: Type Of Brushmentioning
confidence: 99%
“…Diversos países já têm estudos comparando diferentes métodos de rastreio em grupos populacionais distintos [50][51][52][53][54][55][56] , contudo, muitos viéses ainda são encontrados devido ao grande número de dados clínicos, laboratoriais e comportamentais.…”
Section: Análise Descritiva Dos Dadosanálise De Frequências E Porcentunclassified